The epidemiology of paediatric electrical injuries in a South African township. Issue 2 (April 2020) - Lack, Vered; Esteves, Martene; Uzoma Nnaji, Lovelyn; Loveland, Jerome A.; Westgarth-Taylor, Christopher
Highlights: The incidence of paediatric electrical burn injuries in Soweto is 7% of all burns. Almost half the study population live in homes with no formal electrical supply. LV injuries are more common, but HV injuries carry greater morbidity and mortality. 83% of injuries were sustained through outdoor exposed wires and electrical fixtures. Biochemistry abnormalities do not reflect clinical presentation or extent of injury. Abstract: Introduction: In South Africa 10% of inhabitants live in informal dwellings with no running water or electricity. Access to electricity may be improvised by redirecting current from existing fixtures. Injuries from contact with connecting wires are known to occur but are scarcely described. Objectives: To describe the epidemiology, presentation and management of electrical burn injuries experienced by Soweto children presenting to Chris Hani Baragwanath Academic Hospital. Materials and methods: A retrospective review of records for children with a diagnosis of an electrical injury between September 2013 and August 2016 was performed. Results: All children presenting with a history of an electrical injury were admitted. 103 cases were included in the study. 91% were low-voltage injuries with no mortalities, and 9% were high-voltage injuries with a 67% mortality rate. Mean age at presentation was 4.5 years. 81% of injuries were caused by outside wires and other illegal installations. There was a decreased frequency of injuries during the winter months. 73% had biochemistry derangements. Total body surface area affected ranged from 0% to 76%. Conclusion: The incidence of electrical injuries in this study was 7% of all burns related admissions. Injuries sustained carried significant morbidity and mortality. The dominant mechanism of injury in this study can be targeted in primary prevention strategies.